Strategic public spending: evidence from Brazil - Silva, Felipe Yamamoto Ricardo da (2022)
This paper studies how incumbents respond after being voted out of office when running for reelection in terms of public spending. We use data from Brazilian municipalities, focusing on the periodical reports of budget executions that allow us to analyze the public finances in the last two months of an election year, when the incumbent mayor knows if he will remain in office for another term. We apply a Regression Discontinuity Design (RDD) for close elections and find that incumbent mayors who lose the election tend to have higher expenses during the last two months in office than those reelected for another term. The estimated effect is particularly strong for the investment expenses.